Ultrasonic impact treatment method for reducing residual stress of titanium alloy thin plate welded structure - ZHANG WENJING; LIU RUI; YU YANG; HUI SONGXIAO; SONG XIAOYUN; QIAN GUANGLU; YE WENJUN (2018)
The invention relates to an ultrasonic impact treatment method for reducing the residual stress of a titanium alloy thin plate welded structure, belonging to the technical field of metal processing. The ultrasonic impact treatment method specifically comprises the following steps: (1) selecting an impact head: carrying out ultrasonic impact treatment on the titanium alloy thin plate welded structure, wherein the shape of the selected impact head is closely relevant with the shape of a welding joint according to a titanium alloy thin plate welding method, the width of a weld joint of the impacthead is narrow during vacuum electron beam welding, a tabular impact head is adopted, and the width of the impact head is 1.5mm-2.5mm; and (2) carrying out ultrasonic impact treatment process, wherein the impact manner is weld toe impact, the impact number of times is 2-4, the impact speed is 150mm/min-300mm/min. According to the ultrasonic impact treatment method, the targeted and selective treatment of the weld joint c